On the design of the annexation experience between splintered and dissociated sectors - خلف, كمال علوان; حمزة, زينب فالح (Journal of Economics and Administrative Sciences, 2012)
The idea of the design of combination Between split – plot and split block means that an experiment conducted with a design formed by combination Between split – plot and split block, and it presents a precise manner to analytic who aimed to make appropriate statistical analysis for the experiment because such design contains four random errors , it make a high precision rather than another designs. The plan and the theoretical analysis were presented with application   to show its idia and the ability to use it in many fields  especially in agricultural experiments field .